Mcm2, but Not Rpa, Is a Component of the Mammalian Early G1-Phase Prereplication Complex - Dimitrova, Daniela S. (The Rockefeller University Press, 1999)
Previous experiments in Xenopus egg extracts identified what appeared to be two independently assembled prereplication complexes (pre-RCs) for DNA replication: the stepwise assembly of ORC, Cdc6, and Mcm onto chromatin, and the FFA-1–mediated recruitment of RPA into foci on chromatin. We have investigated whether both of these pre-RCs can be detected in Chinese hamster ovary (CHO) cells. Early- and late-replicating chromosomal domains were pulse-labeled with halogenated nucleotides and prelabeled cells were synchronized at various times during the following G1-phase. The recruitment of Mcm2 and RPA to these domains was examined in relation to the formation of a nuclear envelope, specification of the dihydrofolate reductase (DHFR) replication origin and entry into S-phase. Mcm2 was loaded gradually and cumulatively onto both early- and late-replicating chromatin from late telophase throughout G1-phase. During S-phase, detectable Mcm2 was rapidly excluded from PCNA-containing active replication forks. By contrast, detergent-resistant RPA foci were undetectable until the onset of S-phase, when RPA joined only the earliest-firing replicons. During S-phase, RPA was present with PCNA specifically at active replication forks. Together, our data are consistent with a role for Mcm proteins, but not RPA, in the formation of mammalian pre-RCs during early G1-phase.